Tirtha; A sprinkle to the soul - Ida Ayu Putu Widya Indah Sari (Bali Tourism Journal, 2018)
Balinese believe water has abilities to cleanse and neutralize sin through ritual. People use water in their various activities that related to religious practices. The functions are divided into two categories. First, it has a profane role and the other type; they used water as sacred material. Profane purpose means any activity to apply water as a material to fulfill daily human needs. While water with holy function, indicates it is used in religious activities. It is called Tirtha. According to legend, Tirtha is an elixir of immortality. There are two methods to obtain Tirtha. Firstly, water is placed in pelinggih pura or merajan to receive blessings from God Almighty. Second, Balinese obtain Tirtha through a ritual that conducted by the priest. Moreover, Balinese people divides several types of holy water, namely tirtha wangsuhpada, tirtha pembersihan, tirtha pengelukatan, tirtha penembak, and tirtha pengentas.